Modifying Role of Somatotrophin On Trabecular Width & Osteoblast Count of Irradiated Long Bones of Young Albino Rats - Abdul Latif Panwhar, Furkhanda Jabeen Dahri, Razia Tariq Qureshi, Mevo Khan Zardari , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2015)
Objective; To evaluate the modifying effect of Somatotrophin in preservating the harmful effect of a-radiation on trabecular width and osteoblast count in long bones of albino rats litters. Study Design: Experimental study. Place & Duration: Experimental work was completed in six month duration at Basic Medical Sciences Institute (BMSI), Jinnah Postgraduate Medical Center (JPMC ) Karachi. Material & Methods: 30 newborn albino rats were taken for this study. They were divided into three groups: Group A (control), Group B was given 5Gy gamma radiation and Group C was given radiation and inj. Somatotrophin (Growth Hormone). Each group was further divided into two subgroups according to their respective period of treatment i.e. 2 and 4 weeks respectively. At the end of their respective period of study the rats were anaesthetized by ether, dissection was done and their long bones humerus and femur taken out, transferred, fixed and processed. 5 [I longitudinal sections were cut with rotatory microtorne. The tissues stained with Goldner's trichrome for visualization of osteoblast cells and trabeculae. Results: A highly significant decrease in osteoblast count and trabecular width was noted in irradiated subgroups compared with control. And highly significant increase in osteoblast count and trabecular width was noted in Somatotrophin treated subgroups as compared to irradiated subgroups. Conclusion: Irradiation causes destruction of bone marrow, trabecular and osteoblast cells while Somatotrophin reverses the damage. Key words: Long bones, Trabeculae, Osteoblast cells, Somatotrophin.